ADVANTAGES OF NEW INNOVATIVE TECHNOLOGIES IN TEACHING MEDICINE BASED ON EVIDENCE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
The introduction of information technologies into the medical education system of our republic is one of the important issues today. The introduction of new innovative technologies into the educational process also creates a number of conveniences for teachers and students of higher educational institutions. With the help of mastering special technology, it is possible to fully achieve the set goal.